Relationship of Parental Guidance with Learning Motivation of Residents Learning Package B at PKBM Farilla Ilmi - Luvi Permata Suci; Ulfi Ulfi; Yuni Annisa (Universitas Negeri Padang, 2019)
The success of students in learning activities is largely determined by how their motivation and learning achievements are, several factors that influence in accordance with the opinion), namely the availability of tools for learning as a supporting tool for learning activities, as a step to support the learning of the availability of educational tools, there is room for learning, family economics that support, in this study researchers will see how parental guidance on the influence of learning motivation. These research goals to explanations about parent influence about B package education for supporting, researcher take guidance, and motivate 60% from 35 participants. parental guidance would be obtained to have an effective impact Because the role of parents and guidance in the environment of a child is very influential, especially in children's learning. the family is an educational institution in a small size, the first and foremost education that is passed by the child, and gets an education from parents, every encouragement or attention will affect every learning development. but in a different scope and determines education in large measures namely the education of the nation, country, and the world.Keyword: Guidance, Influence, Motivation